Polymer-inorganic cation-exchangers containing zirconium hydrophosphate. Regeneration of uranium-loaded form - Perlova, Olga; Dzyazko, Yulia; Perlova, Natalia; Ivanova, Inna; Palchik, Alexey (My University, 2018)
It has been found that polymer-inorganic cation-exchangers, which contain nanoparticles of zirconium hydrophosphate, can be used many times for sorption of uranyl cations from diluted solutions. This is due to the possibility of practically complete regeneration of the loaded sorbents with diluted solutions of NaHCO3 or EDTA. The sample that includes the smallest embedded particles shows the highest regeneration rate.Встановлено, що органо-неорганічні катіоніти, що містять наночастинки гідрофосфату цирконію, можуть бути використані багаторазово для сорбції катіонів уранілу з розбавлених розчинів завдяки ефективній регенерації урранової форми цих сорбентів розбавленими розчинами NaHCO3 чи ЕДТА.
Keywords: organic-inorganic cation-exchangers; zirconium hydrophosphate; uranyl; regeneration of sorbent; polymer-based composite; органо-неорганічні катіоніти; гідро фосфат цирконію; ураніл-іони; десорбція урана (VI); регенерація сорбентів